2017
DOI: 10.3390/molecules22010169
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Plant Secondary Metabolites Modulating Detoxification Genes Expression for Natural Red Palm Weevil Pesticide Development

Abstract: This study aimed to explore the larvicidal and growth-inhibiting activities, and underlying detoxification mechanism of red palm weevil against phenylpropanoids, an important class of plant secondary metabolites. Toxicity of α-asarone, eugenol, isoeugenol, methyl eugenol, methyl isoeugenol, coumarin, coumarin 6, coniferyl aldehyde, diniconazole, ethyl cinnamate, and rosmarinic acid was evaluated by incorporation into the artificial diet. All of the phenylpropanoids exhibited dose- and time-dependent insecticid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
40
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 40 publications
11
40
0
1
Order By: Relevance
“…The enhanced GST activities in these combinations trigger the solubility of target compound, which ultimately promotes the degradation and excretion of compounds from the target host. Previous studies strengthened our findings and coincides with our results, which reported that lethality of the compound regulates the GST activities [ 47 , 48 ]. Furthermore, their findings suggested that less toxic compounds greatly induced target host GST activities.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The enhanced GST activities in these combinations trigger the solubility of target compound, which ultimately promotes the degradation and excretion of compounds from the target host. Previous studies strengthened our findings and coincides with our results, which reported that lethality of the compound regulates the GST activities [ 47 , 48 ]. Furthermore, their findings suggested that less toxic compounds greatly induced target host GST activities.…”
Section: Discussionsupporting
confidence: 93%
“…However, synergistic combinations established in the current study (especially 2.24 mg/mL phytol + 4 mg/mL spores and 2.80 mg/mL phytol + 5 mg/mL spores) found to be the most lethal treatments showed the reduced activity of GST. These findings are similar to the results of AlJabr et al [ 47 ], who also reported similar GST activity of coumarin-fed red palm weevil larvae. Furthermore, their findings suggested that the most lethal treatment targeted the enzymatic activities of GST, which ultimately led towards the reduction in GST response by masking their enzymatic activities.…”
Section: Discussionsupporting
confidence: 92%
“…Fungal infection evades the host defense mechanism by triggering complex biochemical interactions in the form of series of events through cuticle adhesion, penetration, proliferation, and toxin production, which ultimately lead to the host mortality [29,[31][32][33]. On the other hand, plant secondary metabolites are known antagonists that act by interfering with the signaling of the nervous and cellular systems to overcome the target host defense mechanism [34][35][36][37][38]. Therefore, the combined application is considered as a promising approach due to the differences in their mechanism of actions.…”
Section: Discussionmentioning
confidence: 99%
“…These natural compounds have shown to be effective in agricultural pest management, as they function as antifeedant, growth inhibitors, toxic, repellent, fumigant, attractant etc. and also causes moulting disruption, respiratory inhibition, pheromone-based behavioural adaptations, oviposition deterrence and fecundity reduction against target pest populations (AlJabr et al, 2017;Koul, 2008;Nawaz et al, 2017). Majority of plant secondary metabolites are untapped and are of particular interest in insecticide development (Isman, 2006;Miresmailli and Isman, 2014).…”
Section: Isolation and Identification Of Insect Antifeedant Compoundmentioning
confidence: 99%